0 pour tout kq Inversibilité Un processus MA est inversible sil possède une

0 pour tout kq inversibilité un processus ma est

This preview shows page 11 - 12 out of 12 pages.

?(𝑘) = 0 pour tout k>q. Inversibilité Un processus MA est inversible s’il possède une représentation ?𝑅(∞) . III. Les processus Autorégressifs-Moyennes mobiles (ARMA) Un modèle ARMA combine les deux modèles AR et MA. 1. Le modèle ARMA(1,1) 𝑋 𝑡 − 𝜙 1 𝑋 𝑡−1 = 𝜙 0 + 𝜀 𝑡 − 𝜃 1 𝜀 𝑡−1 La partie à gauche c’est le modèle AR et la partie à droite c’est le modèle MA. a. Propriétés 𝐸(𝑋 𝑡 ) − 𝜙 1 𝐸(𝑋 𝑡−1 ) = 𝐸(𝜀 𝑡 ) − 𝜃 1 𝐸(𝜀 𝑡−1 ) 𝐸(𝜀 𝑡 ) = 𝐸(𝜀 𝑡−1 ) = 0 𝐸(𝑋 𝑡 ) − 𝜙 1 𝐸(𝑋 𝑡−1 ) = 𝜙 0 Sous la condition de stationnarité, 𝐸(𝑋 𝑡 ) = 𝐸(𝑋 𝑡−1 ) , alors 𝐸(𝑋 𝑡 ) = 𝜙 0 1−𝜙 1 . Quand 𝜙 0 = 0 , on a 𝑋 𝑡 − 𝜙 1 𝑋 𝑡−1 = 𝜀 𝑡 − 𝜃 1 𝜀 𝑡−1 . On multiplie à droite et à gauche par 𝜀 𝑡 , 𝑋 𝑡 𝜀 𝑡 − 𝜙 1 𝑋 𝑡−1 𝜀 𝑡 , = 𝜀 𝑡 2 − 𝜃 1 𝜀 𝑡 𝜀 𝑡−1 𝐸(𝑋 𝑡 𝜀 𝑡 ) − 𝜙 1 𝐸(𝑋 𝑡−1 𝜀 𝑡 ) = 𝐸(𝜀 𝑡 2 ) − 𝜃 1 𝐸(𝜀 𝑡 𝜀 𝑡−1 ) On a déjà montré que pour un modèle AR(1) : 𝐸[𝑋 𝑡 𝜀 𝑡+1 ] = 0 . Sous l’hypothèse de stationnarité 𝐸[𝑋 𝑡−1 𝜀 𝑡 ] = 0 . 𝐸(𝜀 𝑡 𝜀 𝑡−1 ) = 0 . 𝐸(𝑋 𝑡 𝜀 𝑡 ) = 𝐸(𝜀 𝑡 2 ) = 𝜎 𝜀 2 On réécrit le modèle sous la forme suivante : 𝑋 𝑡 = 𝜙 1 𝑋 𝑡−1 + 𝜀 𝑡 − 𝜃 1 𝜀 𝑡−1 𝑉(𝑋 𝑡 ) = 𝜙 1 2 𝑉(𝑋 𝑡−1 ) + 𝑉(𝜀 𝑡 ) + 𝜃 1 2 𝑉(𝜀 𝑡−1 ) − 2𝜙 1 𝜃 1 ?𝑜𝑣(𝑋 𝑡−1 , 𝜀 𝑡−1 ) . ?𝑜𝑣(𝑋 𝑡−1 , 𝜀 𝑡−1 ) = 𝐸(𝑋 𝑡−1 𝜀 𝑡−1 ) − 𝐸(𝑋 𝑡−1 )𝐸(𝜀 𝑡−1 ) = 𝐸(𝑋 𝑡−1 𝜀 𝑡−1 )
Image of page 11
Sous l’hypothèse de stationnarité : 𝑉(𝑋 𝑡 ) = 𝑉(𝑋 𝑡−1 ) , 𝑉(𝜀 𝑡 ) = 𝑉(𝜀 𝑡−1 ) = 𝜎 𝜀 2 et 𝐸(𝑋 𝑡 𝜀 𝑡 )𝐸(𝑋 𝑡−1 𝜀 𝑡−1 ) = 𝜎 𝜀 2 . On a alors, 𝑉(𝑋 𝑡 ) = 𝜙 1 2 𝑉(𝑋 𝑡 ) + 𝜎 𝜀 2 + 𝜃 1 2 𝜎 𝜀 2 − 2𝜙 1 𝜃 1 𝜎 𝜀 2 𝑉(𝑋 𝑡 ) = 𝜙 1 2 𝑉(𝑋 𝑡 ) + (1 + 𝜃 1 2 − 2𝜙 1 𝜃 1 )𝜎 𝜀 2 𝑉(𝑋 𝑡 ) = (1 + 𝜃 1 2 − 2𝜙 1 𝜃 1 )𝜎 𝜀 2 1 − 𝜙 1 2 b. Ecriture MA(∞) 𝑋 𝑡 − 𝜙 1 𝑋 𝑡−1 = 𝜀 𝑡 − 𝜃 1 𝜀 𝑡−1 (1 − 𝜙 1 ?)𝑋 𝑡 = (1 − 𝜃 1 ?)𝜀 𝑡 𝜙(?) = 1 − 𝜙 1 ? et 𝜃(?) = 1 − 𝜃 1 ? 𝑋 𝑡 = 𝜃(?) 𝜙(?) 𝜀 𝑡 = 𝜓(?)𝜀 𝑡 = (1 + 𝜓 1 ? + 𝜓 2 ? 2 + ⋯ )𝜀 𝑡 𝑋 𝑡 = ∑ 𝜓 ? 𝜀 𝑡−? ?=0 = 𝜀 𝑡 + 𝜓 1 𝜀 𝑡−1 + 𝜓 2 𝜀 𝑡−2 + ⋯ 𝜃(?) = 𝜙(?)𝜓(?) ↔ 1 − 𝜃 1 ? = (1 − 𝜙 1 ?)(1 + 𝜓 1 ? + 𝜓 2 ? 2 + ⋯ ) 1 − 𝜃 1 ? = 1 + 𝜓 1 ? + 𝜓 2 ? 2 + ⋯ − 𝜙 1 ? − 𝜙 1 𝜓 1 ? 2 − 𝜙 1 𝜓 2 ? 3 + ⋯ 1 − 𝜃 1 ? = 1 + (𝜓 1 − 𝜙 1 )? + (𝜓 2 − 𝜙 1 𝜓 1 )? 2 + ⋯ { −𝜃 1 = 𝜓 1 − 𝜙 1 𝜓 2 − 𝜙 1 𝜓 1 = 0 ↔ { 𝜓 1 = 𝜙 1 − 𝜃 1 𝜓 2 = 𝜙 1 𝜓 1 = 𝜙 1 (𝜙 1 − 𝜃 1 ) Et ainsi de suite pour les autres coefficients.
Image of page 12

You've reached the end of your free preview.

Want to read all 12 pages?

  • Spring '14

What students are saying

  • Left Quote Icon

    As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

    Student Picture

    Kiran Temple University Fox School of Business ‘17, Course Hero Intern

  • Left Quote Icon

    I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

    Student Picture

    Dana University of Pennsylvania ‘17, Course Hero Intern

  • Left Quote Icon

    The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

    Student Picture

    Jill Tulane University ‘16, Course Hero Intern

Stuck? We have tutors online 24/7 who can help you get unstuck.
A+ icon
Ask Expert Tutors You can ask You can ask ( soon) You can ask (will expire )
Answers in as fast as 15 minutes
A+ icon
Ask Expert Tutors